The effect of magnesium on the corrosion of hot‐dip galvanized steel in chloride containing environments. Issue 9 (17th February 2014) - Keppert, T. A.; Luckeneder, G.; Stellnberger, K.‐H.; Commenda, C.; Mori, G.; Antrekowitsch, H.
<x xml:space="preserve">Abstract</x> In this work, three different hot‐dip galvanizing alloys ZnAl0.2, ZnAl5, and ZnAl2Mg2 were tested in non‐standardized salt spray tests. In those non‐standardized salt spray tests, samples were exposed to different pH values, calcium and magnesium ions. The corrosion products formed on the alloys in different conditions were analyzed with XRD and Raman spectroscopy. Additionally, the corrosion behavior of the samples was investigated by studying cross‐section cuts with SEM. By analyzing the corrosion products formed on different samples a theory about the beneficial effect of magnesium in terms of corrosion behavior was developed.